Effects of Learning through SQ4R and Mind Mapping in Thai Language Subject on Reading Comprehension and Attitudes of Secondary School Students - เพ่งสุข, วัชนันท์; คงเรือง, สุภัทรา; รุจิโมระ, จริยาภรณ์ (Journal of Educational Review Faculty of Education in MCU, 2018)
Effects of learning through SQ4R and Mind Mapping in Thai language subject on reading comprehension and attitudes of secondary school students. The sample group was acquired through multi-stage sampling.It consisted of 2 Matthayom 1 classrooms with a total of 60 students studying at Lumpleechanupatham School in Semester 1, Academic Year 2017. Drawing was employed to divide the students into 2 groups- one group was a control group and they learned through teacher manual office of the basic education commission and the other was an experiment group and they learned through the SQ4R and mind mapping. The experiment took 20 hours. Research instruments included 1) lesson plans that incorporated SQ4R and mind mapping through through teacher manual office of the basic education commission; 2) a reading comprehension test and 3) an attitude test toward Thai language subject. Quasi-experimental research was employed. Pre and post experimental tests were conducted. Statistics used to analyze the data was Multivariate of Analysis of Variance (MANOVA).